The interplay between foreign direct investment, security and European integration: The case of the Central and Eastern European countries - Carmen Raluca Stoian; Roger Vickerman (University of Kent, Department of Economics, 2005)
A bi-directional relationship between FDI and economic reforms in ten Central European countries is tested, along with the role of the EU in breaking a potential vicious circle of insecurity, little investment, slow reforms, low prospects of EU membership and hence high insecurity. Using panel data regressions and a system of simultaneous equations, we find evidence that the prospect of EU membership has enhanced FDI in the less reformist candidates and that trade integration and increased EU financial assistance have improved FDI in the CEECs.
Keywords: F2; C2; C3; P26; 330; Foreign direct investment determinants; economic transition; economic reforms; Central and Eastern Europe